(3MGTjI Ydi GdcTGas - (3YeGO GdOjf jMji Hf bGSe GdYdhj Gdjefis
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd bQBfg GdYXje aCMHHJ Cf CLeY cJGHkG BNQ CLeY ajg Hjf eG PcQ ai GdcJGHjf ef GdCHMGK GddWjaI s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI Gdcga s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs